Advanced nutrition and dietetics in nutrition support - Hickson, Mary, 1966-; Smith, Sara, 1970- (Advanced nutrition and dietetics (BDA), 2018)
Written in conjunction with the British Dietetic Association, Advanced Nutrition and Dietetics in Nutrition Support I provides a thorough and critical review of the fundamental and applied literature in nutrition support.